2013
DOI: 10.1371/journal.pone.0070420
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Clinical and Cost Outcomes of a Centralized Approach to Acute Stroke Care in London: A Comparative Effectiveness Before and After Model

Abstract: BackgroundIn July 2010 a new multiple hub-and-spoke model for acute stroke care was implemented across the whole of London, UK, with continuous specialist care during the first 72 hours provided at 8 hyper-acute stroke units (HASUs) compared to the previous model of 30 local hospitals receiving acute stroke patients. We investigated differences in clinical outcomes and costs between the new and old models.MethodsWe compared outcomes and costs ‘before’ (July 2007–July 2008) vs. ‘after’ (July 2010–June 2011) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 9 publications
1
85
0
Order By: Relevance
“…Some of these, such as the apparent fall in mortality rates after the reorganisation of acute stroke services in London, have been widely publicised 5 and could have important implications nationwide. Differences among centres participating in cluster-randomised trials, in the proportion of stroke admissions included, could also seriously affect the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these, such as the apparent fall in mortality rates after the reorganisation of acute stroke services in London, have been widely publicised 5 and could have important implications nationwide. Differences among centres participating in cluster-randomised trials, in the proportion of stroke admissions included, could also seriously affect the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…One study of A&E centralisation in Sheffield 15 found that the centralised model was more costly. A more recent study of the centralisation of stroke services in London 16 was more positive in its findings.…”
Section: Reconfiguration and The Evidence To Support Itmentioning
confidence: 95%
“…The new model has been formally evaluated. 16 The conclusion of this before-and-after study was that London's centralised model for acute stroke care had reduced mortality for a reduced cost per patient, predominantly as a result of reduced hospital length of stay. However, the authors recognise the limitations of a before-and-after study versus a randomised control trial and noted that further research would be required to assess whether or not the London model is viable in other geographical and clinical settings.…”
Section: Professional Guidance and Evidence From The Literaturementioning
confidence: 99%
“…Telestroke networks are important tools for diagnostic and treatment support of acute stroke patients for less well-resourced hospitals and also for the referral of selected patients to more qualified institutions. Telestroke has been proved to be a safe, efficient and cost-effective strategy for stroke care 30 .…”
Section: Trained Specialists and Telemedicinementioning
confidence: 99%